2004
DOI: 10.1298/jjpta.7.35
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of Evidence Based Physiotherapy in Patients with Facial Nerve Paresis

Abstract: Abstract. A variety of physiotherapeutic approaches have been tried out during the past 25 years to alleviate the plight of patients with peripheral facial nerve paresis. The objective of this review was to assess the effectiveness of physiotherapy in patients with facial nerve paresis. Trials were identified by computerised searches of biomedical databases, reference lists, and by contacting investigators. Selection criteria were randomised controlled trials of physiotherapy for the improvement of sequelae of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…People suffering the sequelae of facial nerve paresis may be referred to physiotherapists since the medical practitioner's options are limited to invasive treatments such as injection of Botulinum toxin A and surgical reconstruction (Beurskens et al 2005). Although a variety of physiotherapy interventions have been used to treat facial nerve paresis (Beurskens et al 2004a), randomised controlled trials have found no evidence in favour of one intervention over another (Mosforth and Taverner 1958: electrotherapy vs massage; Ross et al 1991: EMG-biofeedback vs mirror-feedback; Segal et al 1995a: 'small-movement-therapy' vs exercise). Around 1980, mime therapy was developed in the Netherlands specifically for people with facial nerve paresis through collaboration between medical clinicians and mime-actors (Devriese and Bronk 1977).…”
Section: Introductionmentioning
confidence: 99%
“…People suffering the sequelae of facial nerve paresis may be referred to physiotherapists since the medical practitioner's options are limited to invasive treatments such as injection of Botulinum toxin A and surgical reconstruction (Beurskens et al 2005). Although a variety of physiotherapy interventions have been used to treat facial nerve paresis (Beurskens et al 2004a), randomised controlled trials have found no evidence in favour of one intervention over another (Mosforth and Taverner 1958: electrotherapy vs massage; Ross et al 1991: EMG-biofeedback vs mirror-feedback; Segal et al 1995a: 'small-movement-therapy' vs exercise). Around 1980, mime therapy was developed in the Netherlands specifically for people with facial nerve paresis through collaboration between medical clinicians and mime-actors (Devriese and Bronk 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Ballestero-P erez et al [82], showed that, although the standard conservative approach represents the best option for the management of carpal tunnel syndrome, the addition of nerve gliding exercises may improve the patient recovery by accelerating the rehabilitation process and avoiding the surgical intervention. In Bell's palsy, an acute disorder of the facial nerve, different physical rehabilitation protocols, based on active therapy, passive therapy or a combination of passive and active methods (e.g., massage/manipulation with active exercise regime), induced an improvement of facial movement and/or function [83]. Instead, other studies showed that the facial exercises, including strengthening and stretching, endurance, therapeutic and facial mimic exercises, seem to not produce significantly more improvement than the control treatment or no treatment [84,85].…”
Section: Clinical Studies Of Exercise and Peripheral Nerve Injurymentioning
confidence: 99%
“…The effects of mime therapy for patients with longstanding (at least 9 months) squeal of unilateral peripheral facial paralysis were www.ijsrp.org evaluated. Mime therapy, including auto massage, relaxation exercises, inhibition of Synkinesis, coordination exercises, and emotional expression exercises were performed (7) .On the basis of present evidence, mime therapy is a good treatment of choice for patients with long standing facial paralysis (8) .Multidimensional therapies were used for treatment of facial palsy. Most recommended treatments were electric stimulation (9).…”
Section: • Birth Traumamentioning
confidence: 99%